2017
DOI: 10.1149/2.1291713jes
|View full text |Cite
|
Sign up to set email alerts
|

Metal Salt Solutions as a Simulant for the Chemistry in Crevices of Nickel Alloy 625

Abstract: The development of a critical crevice solution plays an important role in crevice corrosion propagation in nickel alloy 625. In this investigation, the polarization response of alloy 625 in a set of simulated crevice chemistries using metal chloride salts has been studied. Specifically, solutions were made from NiCl 2 , CrCl 3 , FeCl 2 , MoCl 3, and NbCl 5 in the same stoichiometric ratio as they appear in the alloy and ranging in concentration from 3.0 to 5.0 molal (m). It was found that Mo and Nb contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, the models show that early propagation occurs in an alloy 625 solution concentration less than 1 M, far below the solution concentration necessary for an active to passive transition in alloy 625. We have previously shown that an active to passive transition in alloy 625 does not develop in the solution of cations below 3 m. 7 In comparison, here, after 5.76 ks of propagation the solution composition was approximately 0.9 M alloy 625 (Fig. 5, g = 40 × 10 −6 m).…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…In addition, the models show that early propagation occurs in an alloy 625 solution concentration less than 1 M, far below the solution concentration necessary for an active to passive transition in alloy 625. We have previously shown that an active to passive transition in alloy 625 does not develop in the solution of cations below 3 m. 7 In comparison, here, after 5.76 ks of propagation the solution composition was approximately 0.9 M alloy 625 (Fig. 5, g = 40 × 10 −6 m).…”
Section: Discussionmentioning
confidence: 42%
“…This model solution consisted of 0.6 M NaCl, the initial OW crevice environment (converted to molality using a solution density of 1.022 g cm −3 , OLI) and, to represent the anodic dissolution products of Ni, Cr, Fe, Mo and Nb from alloy 625 we used the metal salts CrCl 3 , NiCl 2 , FeCl 2 , MoCl 3 , and [Nb 2 O 5 + 10HCl]. 7 The relative mass% of metal cations in the simulation was that of the alloy in the experimental study and equal to Ni-22.36 wt% Cr, 8.76% Mo, 3.74% Fe and 1% Nb (sub stochiometric w.r.t. Nb).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall, the Flade potentials for alloy 625 in simulated CCS are on the order of −0.2 V to 0.0 V vs SCE. 31 As such, for the case of alloy 625, breakdown most likely owes to transpassivity. There is a wealth of literature on the transpassivity of nickel alloys and these investigations typically focus Cr(III) oxidation to soluble Cr +6 in the transpassive region and little attention is given to the role of other alloying elements.…”
Section: Discussionmentioning
confidence: 99%